Six Ways of Looking at Context - Maley, Alan (Journal of NELTA, 2018)
This short article is an attempt to specify more clearly what we might mean by the term ‘context’. I examine six aspects of context: Physical, ametrial and economic; Socio-poloitical and religious; l Linguistic; Philosophical and educational; Family and peer group; Psychological, relational and affective. I discuss each of these relating to the classroomteaching and learning of English. Journal of NELTA, Vol 20 No. 1-2, December 2015, Page: 1-4